2020
DOI: 10.3389/fmicb.2020.01938
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Temporal Succession of Bacterial Communities in Early Marine Biofilms in a Portuguese Atlantic Port

Abstract: Marine biofilms are known to influence the corrosion of metal surfaces in the marine environment. Despite some recent research, the succession of bacterial communities colonizing artificial surfaces remains uncharacterized in some temporal settings. More specifically, it is not fully known if bacterial colonizers of artificial surfaces are similar or distinct in the different seasons of the year. In particular the study of early biofilms, in which the bacterial cells communities first adhere to artificial surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 125 publications
(177 reference statements)
4
24
1
Order By: Relevance
“…Cyanobacteria and Planctomycetes were also relevant phyla on biofouling and biofilm samples. Studies on biofouling growth on stainless steel plates in the same port marina as the present study, showed that the most abundant phyla were Cyanobacteria, Proteobacteria, Bacteroidetes, and Fusobacteria [31] as well as Proteobacteria, Bacteroidetes, Cyanobacteria, and Actinobacteria [53]. The average relative abundance of the main phyla for each type of samples (biofouling from the floating platform, biofilm from the planting media and water), is displayed in Figure 8, being the most abundant phyla Proteobacteria and Bacteroidetes (Appendix A Figure A1 shows the top 10 phyla found per sample analyzed).…”
Section: Assessment Of Microbial Diversity In the Fwi And Watersupporting
confidence: 67%
See 4 more Smart Citations
“…Cyanobacteria and Planctomycetes were also relevant phyla on biofouling and biofilm samples. Studies on biofouling growth on stainless steel plates in the same port marina as the present study, showed that the most abundant phyla were Cyanobacteria, Proteobacteria, Bacteroidetes, and Fusobacteria [31] as well as Proteobacteria, Bacteroidetes, Cyanobacteria, and Actinobacteria [53]. The average relative abundance of the main phyla for each type of samples (biofouling from the floating platform, biofilm from the planting media and water), is displayed in Figure 8, being the most abundant phyla Proteobacteria and Bacteroidetes (Appendix A Figure A1 shows the top 10 phyla found per sample analyzed).…”
Section: Assessment Of Microbial Diversity In the Fwi And Watersupporting
confidence: 67%
“…Cyanobacteria and Planctomycetes were also relevant phyla on biofouling and biofilm samples. Studies on biofouling growth on stainless steel plates in the same port marina as the present study, showed that the most abundant phyla were Cyanobacteria, Proteobacteria, Bacteroidetes, and Fusobacteria [31] as well as Proteobacteria, Bacteroidetes, Cyanobacteria, and Actinobacteria [53]. The beta-diversity analyzed through the principal coordinates analysis (PCoA) ( Figure 9) showed a clear distinct communities' composition developed in the biofouling and biofilm compared with the water.…”
Section: Assessment Of Microbial Diversity In the Fwi And Watersupporting
confidence: 58%
See 3 more Smart Citations